2022
DOI: 10.3389/fpsyg.2022.980570
|View full text |Cite
|
Sign up to set email alerts
|

The role of farmers’ green values in creation of green innovative intention and green technology adoption behavior: Evidence from farmers grain green production

Abstract: Grain for Green Project (GGP) is one of China’s important ecological restoration projects. The key rationale of this Program is to decrease soil erosion and develop ecological conditions. The agricultural sector is putting efforts to promote green innovation and production among farmers to achieve the targets of ecological restoration projects. However, farmers’ green values could play a constructive role in building green innovative intention and green technology adoption behaviors. Based on the unified theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…The result shows that the younger generation of farmers tend to have stronger intention to adopt modern agricultural as they are not greatly influenced by social influences such as their family member, friends and other fellow farmers. This finding supported the assertion made by Gao et al (2022) that emphasized that social factors offer non-conclusive effect on farmers' adoption behaviour on modern agricultural technology. It also agreed to assertion that described eldest farmers are afraid to take risk to adopt modern agricultural technology compared to younger generation of farmers (Mwangi & Kariuki, 2015;Sennuga et al, 2020).…”
Section: Partial Moderating Effectsupporting
confidence: 89%
See 1 more Smart Citation
“…The result shows that the younger generation of farmers tend to have stronger intention to adopt modern agricultural as they are not greatly influenced by social influences such as their family member, friends and other fellow farmers. This finding supported the assertion made by Gao et al (2022) that emphasized that social factors offer non-conclusive effect on farmers' adoption behaviour on modern agricultural technology. It also agreed to assertion that described eldest farmers are afraid to take risk to adopt modern agricultural technology compared to younger generation of farmers (Mwangi & Kariuki, 2015;Sennuga et al, 2020).…”
Section: Partial Moderating Effectsupporting
confidence: 89%
“…Social factors have been subjected to debates over its influence over farmers' adoption behaviour on modern agricultural technology. For instance, Gao et al (2022) in their literature reviews emphasized that social factors offer non-conclusive effect on farmers' adoption behaviour on modern agricultural technology despite mentioning social factors' negative relationship with farmers' adoption behaviour as opined by Feder and Umali (1993). Similarly, a study conducted by Han et al (2022) has concluded that farmers' social capital which refers to the enabling relationship linkages among farmers in a certain community has shown mixed impacts on farmers' willingness to adopt modern agricultural technology depending to specific zones in China.…”
Section: Social Influencementioning
confidence: 99%